2005
DOI: 10.1159/000085839
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Function, Cytokine and IGF-IGFBP Interactions in Cystic Fibrosis Patients

Abstract: Background/Aims: Thyroid function impairment has been sporadically described in cystic fibrosis (CF) and ascribed to iodine overload or selenite deficiency. In this study we evaluated thyroid function in CF in order to verify these data and to evaluate if the modifications were related to serum levels of markers of inflammation and growth factors that we have previously shown to be altered in CF. Methods: Seventeen young adult CF patients and 18 age-matched controls were enrolled in this study. The diagnosis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 34 publications
0
6
0
1
Order By: Relevance
“…A recent small study by Volta et al showed that there was no significant thyroid dysfunction observed in 17 CF patients compared to controls, and concluded that this may be related to improved nutritional status and lack of iodinecontaining medication use (12). The present study aimed to assess thyroid function status in both ambulatory and hospitalized CF patients in a larger cohort.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…A recent small study by Volta et al showed that there was no significant thyroid dysfunction observed in 17 CF patients compared to controls, and concluded that this may be related to improved nutritional status and lack of iodinecontaining medication use (12). The present study aimed to assess thyroid function status in both ambulatory and hospitalized CF patients in a larger cohort.…”
Section: Introductionmentioning
confidence: 81%
“…Although development of goiter and hypothyroidism in patients with CF has been described since the 1970s, especially in the setting of excess iodine exposure (2,3), a recent study of 17 patients reported no significant thyroid dysfunction in patients with CF (12). Studies to determine the potential mechanism of thyroid dysfunction in patients with CF have reported conflicting results.…”
Section: Thyroid Function In Cystic Fibrosis 877 Discussionmentioning
confidence: 99%
“…A recent study by Volta et al (9) suggested no significant thyroid dysfunction in 17 CF patients compared to age-and sex-matched controls, and they concluded that this may be related to improved nutritional status and lack of iodine including pulmonary expectorant use. The largest study assessing thyroid dysfunction in patients with CF was presented by Sun dose iodine developed goiter, and 83% of those developed hypothyroidism.…”
Section: Discussionmentioning
confidence: 98%
“…An increased incidence of goiter with or without associated hypothyroidism as a complication of receiving pulmonary expectorants containing iodides, low T3 and/or low T 4 and rT 3 levels with increased basal and TRH-stimulated TSH levels, impaired peripheral conversion of T4 to T3 due to selenite deficiency as a result of malnutrition have been reported in particular in patients with CF in previous studies (5)(6)(7)(8). However, unlike previously published studies, normal thyroid function tests in patients with CF compared with normal healthy subjects is available in the literature (9). In present study, we aimed to investigate the prevalence of thyroid dysfunction in children with CF (i) and evaluate general characteristics of these patients in Turkey (ii).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation